2020
DOI: 10.4236/ojbm.2020.81003
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Direct Investment, Trade Openness and Economic Growth: Evidence from Ghana

Abstract: This article investigates the relationship among foreign direct investment, trade openness and economic growth in Ghana taking the period of post-liberalization covering 1975-2017. The Augmented Dickey-Fuller (ADF) test for unit root, regression analysis, descriptive analysis, and Pearson correlation was used to investigate the relationships. ADF test for unit root result shows all variables to be integrated of order one, that is they are stationary after the first difference. The study extracted and used seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 26 publications
(21 reference statements)
3
17
0
Order By: Relevance
“…In achieving the objectives of the study, the following null hypotheses are tested: (i) trade openness has no significant effect on economic growth of Ghana, (ii) quality of institution has no significant effect on economic growth of Ghana and (iii) quality of institution and trade openness have no complementarity effect on economic growth of Ghana. The study contributes to past literature pertaining to trade openness and economic growth in that, past studies, especially on Ghana (see: Adams & Atsu, 2014;Adu, 2013;Asiedu, 2013;Ehigiamusoe & Lean, 2018;Khobai et al, 2018;Mireku et al, 2017;Nketiah et al, 2019;Oteng-Abayie & Frimpong, 2006;Sakyi, 2011;Sakyi et al, 2015a) in attempt to assess the impact of trade openness on economic growth of Ghana ignore quality of institutions as a variable in the analysis and as a result fail to examine how quality of institutions influence the impact of trade openness on economic growth. Therefore, this study contributes to literature by incorporating this issue in the analysis.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…In achieving the objectives of the study, the following null hypotheses are tested: (i) trade openness has no significant effect on economic growth of Ghana, (ii) quality of institution has no significant effect on economic growth of Ghana and (iii) quality of institution and trade openness have no complementarity effect on economic growth of Ghana. The study contributes to past literature pertaining to trade openness and economic growth in that, past studies, especially on Ghana (see: Adams & Atsu, 2014;Adu, 2013;Asiedu, 2013;Ehigiamusoe & Lean, 2018;Khobai et al, 2018;Mireku et al, 2017;Nketiah et al, 2019;Oteng-Abayie & Frimpong, 2006;Sakyi, 2011;Sakyi et al, 2015a) in attempt to assess the impact of trade openness on economic growth of Ghana ignore quality of institutions as a variable in the analysis and as a result fail to examine how quality of institutions influence the impact of trade openness on economic growth. Therefore, this study contributes to literature by incorporating this issue in the analysis.…”
Section: Introductionmentioning
confidence: 76%
“…Similarly, Nketiah et al (2019) examine the relationship between foreign direct investment, trade openness and economic growth using annual time series data covering the period 1975-2017. Employing the ordinary least squares as estimation technique, the study finds that trade openness exerts a significant positive impact on economic growth whereas inflation (foreign direct investment) has insignificant positive (insignificant negative) effect on economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have used different variables and approaches in finding the determinants of GDP growth. Nketiah et al [10] estimated Foreign Direct Investment on Trade Openness on Economic Growth: Evidence from Ghana from 1975 to 2017. The analysis was based on time series which indicated that trade openness is a main factor affecting Economic growth.…”
Section: Gdp Growthmentioning
confidence: 99%
“…They found that the variables were cointegrated. Olabisi and Lau (2018) Nketiah, Cai, Adjei, and Boamah (2019) searched the effects of FDI, trade openness on GDP growth for Ghana throughout 1975 and 2017 using different techniques and found that the main factor affecting economic growth is trade openness in Ghana. Wiredu, Nketiah, and Adjei (2020) created a panel for four West African countries covering the years 1998-2017 and investigated the link between economic growth, FDI, and trade openness, and found a positive and significant relation between the variables.…”
Section: Literature Reviewmentioning
confidence: 99%